Recovery of cellulose and lignin from Eucalyptus by-product and assessment of cellulose enzymatic hydrolysis. (June 2022) - Roberto Paz Cedeno, Fernando; Belon de Siqueira, Breno; Gabriel Solorzano Chavez, Eddyn; Ulises Miranda Roldán, Ismael; Moreira Ropelato, Leonardo; Paul Martínez Galán, Julián; Masarin, Fernando
Abstract: In this study, a Eucalyptus by-product was fractionated into cellulose and lignin by pretreatment with NaClO2 to obtain α-cellulose, and hydrothermal pretreatment followed by sulfite-NaOH to obtain cellulose and lignin. The recovered celluloses were chemically and structurally characterized and enzymatically hydrolyzed using commercial enzyme preparations. The α-cellulose and cellulose treated with sulfite-NaOH had cellulose contents of 70.1% and 61.1%, respectively. α-cellulose hydrolyzed with Celluclast showed potential for cello-oligosaccharides formation, resulting in a maximum conversion of 30%, while Cellic CTec 2 resulted in 100% conversion to glucose, whereas cellulose treated with sulfite-NaOH showed potential for conversion to glucose with Cellulcast (44%) and Cellic CTec 2 (78%). The liquor from the sulfite-NaOH process resulted in a 20.8% yield of sulfonated lignin recovery. The use of different pretreatment techniques for the Eucalyptus by-product can be alternatives for the generation of products with high added value and commercial potential, such as cello-oligosaccharides, glucose, and sulfonated lignin. Graphical abstract: Image 1 Highlights: Eucalyptus by-product treated with NaClO2 was hydrolyzed to cello-oligosaccharides. Eucalyptus by-product thermotreated and treated with sulfite-NaOH was hydrolyzed to glucose. Glucose hydrolysate has potential for 2G ethanol production. Sulphonated lignin was recovered from sulfite-NaOH hydrolysis liquor. Sulphonated lignin can be used for energy cogeneration.